Comparison of the fecal bacterial microbiota of healthy and diarrheic foals at two and four weeks of life - Schoster, A. (BMC Vet Res, 2017)
BACKGROUND: Diarrhea in foals affects up to 60% of foals during the first six months of life. The effect of diarrhea on the fecal bacterial microbiota in foals has not been investigated. Little is known on the fecal bacterial microbial richness and diversity of foals at a young age. The objective was to compare the fecal bacterial microbiota of healthy foals to foals with diarrhea at two and four weeks of life. METHODS: Fecal samples were collected from foals (n = 20) at 1–14 (T1) and 15–28 (T2) days of age and analyzed using high throughput sequencing. Differences in relative abundance of bacterial taxa, alpha diversity and beta diversity indices were assessed between age-matched foals with diarrhea (n = 9) and healthy foals (n = 11), and between time points. RESULTS: Differences in microbial community composition based on time point and health status were observed on all taxonomic levels. Of 117 enriched species in healthy foals at T2, 50 (48%) were Lachnospiraceae or Ruminococcaceae. The Chao richness index was increased in healthy foals at T2 compared to T1 (p = 0.02). Foals with diarrhea had a significantly lower richness index than non-diarrheic foals at T2 (p = 0.04). Diarrhea had an inconsistent effect, while time point had a consistent effect on microbial community structure. CONCLUSIONS: Preventative and therapeutic measures for diarrhea should focus on maintaining bacterial microbiota richness. Lachnospiraceae and Ruminococcaceae were underrepresented in foals with diarrhea. These should be evaluated further as potential therapeutic options. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12917-017-1064-x) contains supplementary material, which is available to authorized users.